A Functional and Practical Taxonomy for the Industrial Implementation of Highly Automated Reverse Manufacturing Cells - Annagiulia Morachioli; Vladimir Sivtsov; Nicolas Rojas; Fabio Bonsignorio (IEEE Open Journal of the Industrial Electronics Society)
While it is a widespread understanding that the sustainability of the global economy requires a transition to a circular economy paradigm where a growing share of the raw materials resources used for the manufacturing of the products are recycled when products reach their end-of-life, still this much-needed transition faces organizational and technical challenges. The key technical and economic bottlenecks are in the automation of disassembly. In this article, we propose a viable functional framework for the systematic analysis, design, and implementation of disassembly cells. This framework consists of two main parts: a systematic categorization of disassembly tasks and a modular and flexible hardware (HW)/software (SW) architecture of a disassembly cell able to implement the disassembly tasks. We analyze and categorize human manipulation when disassembling a common object of daily working activities as a new companion concept to the more common concept of daily life activities. We tested and validated our methodology on the disassembly of a car suspension.